Penerapan Eksperimen “Balon Reaksi Kimia” untuk Meningkatkan Pemahaman Konsep Perubahan Wujud Benda di Kelas III SD Jatisari 01 Jenggawah Jember - Fitria Dira Novalina; Muhammad Suwignyo Prayogo; Siti Nur Halimah; Iklilah Muzayanah (Universitas Palangka Raya, 2025)
This study aims to describe the implementation of the “chemical reaction balloon” experiment in enhancing students’ understanding of the concept of changes in the states of matter among fifth-grade students at SD Jatisari 1, Jember. The study was motivated by the students’ limited conceptual understanding, which primarily results from teacher-centered instruction and the lack of hands-on learning experiences. Employing a qualitative descriptive approach, the research focuses on the learning process and students’ interactions during the experiment. The activity involves a simple chemical reaction using baking soda and vinegar, which produces gas and inflates a balloon. This observable phenomenon serves as a tangible model to help students comprehend the transformation of matter from solid to liquid and gas. Data were collected through observation, interviews, and documentation. The findings reveal that the implementation of the chemical reaction balloon experiment improved students’ conceptual understanding of changes in the states of matter. Students demonstrated higher enthusiasm, active participation in discussions, and the ability to connect their observations with scientific concepts. Moreover, teachers gained valuable insights into the use of simple experimental methods as effective learning tools in elementary science education. In conclusion, the chemical reaction balloon experiment proved to be an effective learning method for improving conceptual understanding in science, particularly concerning changes in the states of matter. This method provides meaningful learning experiences and fosters scientific thinking through engaging, hands-on activities.